Identification of 9-Core Immune-Related Genes in Bladder Urothelial Carcinoma Prognosis - Na, Lei; Bai, Yu; Sun, Yu; Wang, Zhuo; Wang, Wei; Yuan, Lin; Zhao, Chenghai (Frontiers in Oncology, 2020)
Background: Immune microenvironment within tumors affects initiation, progression and clinical outcome of human cancers. Here we explored an immune-related gene signature associated with prognosis of patients with bladder urothelial carcinoma. Method: The Cancer Genome Atlas (TCGA) database was interrogated for expressions of immune-related genes in bladder urothelial carcinomas. Integrated bioinformatics analyses were performed to identify prognostic factors. Results: 27 immune-related genes were revealed significantly associated with patient’s overall survival (OS) by univariate Cox proportional hazards regression analysis. 9-core immune-related genes including MMP9, PDGFRA, AHNAK, OLR1, RAC3, IGF1, PGF, OAS1 and SH3BP2 were selected to construct a risk score model by multivariate Cox proportional hazards regression analysis. Bioinformatics analyses further validated that risk score could be used as an important independent factor in evaluating prognosis. Conclusion: We established a prognostic immune signature for patients with bladder urothelial carcinoma, which may provide novel targets for prediction and therapy of these patients.